Elaboration of the Algorithm of MLST-Typing of Pandemic and Pre-Pandemic V. cholerae El Tor strains - A. V. Ossin; Ya. M. Krasnov; N. P. Guseva; N. I. Smirnova (Проблемы особо опасных инфекций, 2011)
Molecular typing of pandemic and pre-pandemic cholera vibrio strains was carried out with the help of multi-locus sequence analysis. Application of two MLST schemes based on the sequence of virulence-associated and housekeeping genes demonstrated the last one to be the most effective in differentiation of strains, isolated before and during the seventh cholera pandemic.